2018
DOI: 10.3390/healthcare6040140
|View full text |Cite
|
Sign up to set email alerts
|

How Widely are Supportive and Flexible Food Service Systems and Mealtime Interventions Used for People in Residential Care Facilities? A Comparison of Dementia-Specific and Nonspecific Facilities

Abstract: While improved mealtime practices can reduce agitation, improve quality of life, and increase food intake for people in aged care, the degree of implementation of these strategies is unknown. This study describes food service practices in residential aged care facilities, focusing on units caring for people with dementia. An online survey was distributed to residential aged care facilities for completion by the food service manager (n = 2057). Of the 204 responses to the survey, 63 (31%) contained a dementia-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Of 13 selected international comparison studies, five found little‐to‐no difference between residents living with ADRD in DSCUs and TNHs in terms of nutritional status, case conferences, mealtime experiences, and resident care and attention (Table 6). 93–97 Although not statistically significant, residents with dementia in DSCUs and TNHs were found to be different in terms of age, strength, and mobility in one study (e.g., residents in DSCUs were stronger and younger than residents in TNHs), 94 and in terms of content of case conferences (e.g., fewer case conferences regarding challenging behaviors were conducted in DSCUs compared to TNHs) in another study 95 . However, three studies reported worse outcomes among residents in DSCUs compared to residents in TNHs (e.g., higher rates of antipsychotic medications, social isolation, and burdensome transitions at the end‐of‐life) 98–100 .…”
Section: Resultsmentioning
confidence: 92%
“…Of 13 selected international comparison studies, five found little‐to‐no difference between residents living with ADRD in DSCUs and TNHs in terms of nutritional status, case conferences, mealtime experiences, and resident care and attention (Table 6). 93–97 Although not statistically significant, residents with dementia in DSCUs and TNHs were found to be different in terms of age, strength, and mobility in one study (e.g., residents in DSCUs were stronger and younger than residents in TNHs), 94 and in terms of content of case conferences (e.g., fewer case conferences regarding challenging behaviors were conducted in DSCUs compared to TNHs) in another study 95 . However, three studies reported worse outcomes among residents in DSCUs compared to residents in TNHs (e.g., higher rates of antipsychotic medications, social isolation, and burdensome transitions at the end‐of‐life) 98–100 .…”
Section: Resultsmentioning
confidence: 92%
“…Previous research shows that food intake at RCFs is affected by the dining environment and social interactions at mealtimes (Keller et al., 2015). However, the use of environmental and social strategies to promote food intake is fairly low (Milte et al., 2018). From this study, we know that there are associations between dignity and well‐being and the mealtime environment, but we do not know what factors in the mealtime environment affect dignity and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Yeung et al [ 8 ] attributed public perceptions of food safety to three sources, i.e., bacteria, chemical additives and new technologies such as transgenic technology. Moreover, media reports [ 27 ] a risk prewarning system [ 28 ] and information communication [ 29 ] significantly affect public perceptions of food safety. A study conducted by Hohl et al [ 30 ] with data from 25 European countries identified the three most important exogenous factors and revealed that cross-national diversity may contribute to different perceptions of food safety.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%